From Neonatal Hearing Screening to Intervention: Results of the Dutch Program for Neonatal Hearing Screening in Well Babies - Noëlle Uilenburg; Catharina Van der Ploeg; Rosanne van der Zee; Anneke Meuwese-Jongejeugd; Bert van Zanten (MDPI AG, 2018)
In the Netherlands, Youth Health Care services (YHC) have been carrying out neonatal hearing screening (NHS) in newborns since 2006. The aim of the NHS is to identify children with permanent hearing loss, so that intervention can be started before the age of 4 months. Early detection of hearing loss is important, as children who start intervention early have been shown to develop better. This article describes the structure and performance of the NHS carried out by the YHC, the quality of the program, and the timeliness of the start of intervention. Since its implementation, the NHS has been audited annually in order to monitor the program’s quality. Monitoring reports and data from the Dutch Foundation for the Deaf and Hard of Hearing Child were used in this study. For many years, results have shown the NHS to be a stable screening program of high quality. The participation rate is high, refer percentage low, and the timeliness of the program is continually improving. Although the timeliness of post screening diagnostics and intervention need most improvement as they do not always meet the target times, this has improved over recent years.